Balancing Structure and Autonomy: EFL Tutors’ Psychological Perceptions in Web-based Distance Learning - TONO PALANGNGAN, SUKMAWATI; Sukardi Weda; Nurdin Noni; Rahayu; Wan Yusoff Wan Shaharuddin (Universitas Sulawesi Barat, 2026)
The rapid expansion of web-based distance learning (WBDL) in higher education has significantly changed English as a Foreign Language (EFL) instruction, particularly in universities that implemented a distance learning system where flexibility and technological integration are vital. While most research focuses on technology or students, this study explores how English as a Foreign Language (EFL) tutors at an Indonesian university perceive web-based distance learning. Employing a descriptive qualitative design within an interpretive paradigm conceptually grounded in Qiong's (2017) six-dimension framework, the study analyzes interview data from two experienced tutors. The tutor was intentionally chosen to facilitate an in-depth, rich, and detailed comparative analysis of their subjective psychological perceptions, aligning with the study's interpretive paradigm, which seeks depth over generalizability. The interviews were recorded and transcribed, then thematically analyzed with multiple rounds of open coding, thematic grouping, and interpretive synthesis in order to establish how tutors' perceptions reflected their negotiation between institutional expectations and professional agency. The results illustrate a key tension reflecting the study's central dichotomy: one tutor prioritizes institutional structure and professionalism, while the other emphasizes pedagogical autonomy and learner-centeredness. The study concludes that successful web-based distance learning requires a dynamic psychological balance between the system and autonomy. Practically, these findings suggest that institutions must move beyond mere technical training and provide robust psychological and affective support, recognizing tutors as critical agents in negotiating this balance rather than just as system operators.